Determinants of Knowledge and Behaviours of Indonesian Health Care Providers toward the Prevention of COVID-19 - Yoyok Bekti Prasetyo; Alhisna Fitri Setyamardina; Henik Tri Rahayu; Titih Huriah (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: Due to the high risk of exposure of Health Care Providers (HCPs) at the forefront of the COVID-19 responses, HCPs’ knowledge and prevention behaviors towards COVID-19 have become crucial parts of their job performances.